Political science, public administration, and the rise of the American administrative state - Wing-yee Lee, Eliza (1995)
"Is there a "troublesome cleft" between political science and public administration or a problematic alliance? Examining the historical rise of political science and public administration from the late 19th century to the 1930s shows that political science has played an important role in defining the intellectual space of public administration. Political science historically arose as a project of liberal reform, and public administration was supposed to be part of that project. The technicist and antipolitical bias of public administration was inherent in the ontology of a positivistic political science. Together, they supplied the ideological and institutional apparatus for the transformation of the American liberal tradition and the rise of the administrative state. Re-examining the relationship between politics and administration/political science and public administration requires a critical examination of the theories and methods of both disciplines"
Keywords: Political science - United States; Public administration - United States; Public administration